2007
DOI: 10.1097/01.ico.0000240079.24583.a1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Topical Dry Eye Medications for the Treatment of Keratoconjunctivitis Sicca in a Botulinum Toxin B-Induced Mouse Model

Abstract: The therapeutic effects of dry eye medications in a BTX-B-induced mouse model of KCS are similar to the human response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 35 publications
0
16
0
1
Order By: Relevance
“…In a study with botulinum toxin B-induced mouse model, it was demonstrated that topical antiinflammatory agents, both steroids and cyclosporine A, could restore the tear production and improve the corneal surface. 24 Hyon et al 25 also demonstrated that antiinflammatory treatment improved subjective symptoms and objective signs but had limited effect in increasing tear production. In a recent study, Willen et al compared the efficiency of topical cyclosporine treatment and rewetting eyedrops in contact lens users with dry eye symptoms and found no statistically significant difference between the 2 groups in all objective measurement parameters including corneal staining, Schirmer test results, and BUT scores.…”
Section: Discussionmentioning
confidence: 95%
“…In a study with botulinum toxin B-induced mouse model, it was demonstrated that topical antiinflammatory agents, both steroids and cyclosporine A, could restore the tear production and improve the corneal surface. 24 Hyon et al 25 also demonstrated that antiinflammatory treatment improved subjective symptoms and objective signs but had limited effect in increasing tear production. In a recent study, Willen et al compared the efficiency of topical cyclosporine treatment and rewetting eyedrops in contact lens users with dry eye symptoms and found no statistically significant difference between the 2 groups in all objective measurement parameters including corneal staining, Schirmer test results, and BUT scores.…”
Section: Discussionmentioning
confidence: 95%
“…Corticosteroids are used in the inflammatory process especially in dry eye pathogenesis due to their strong anti-inflammatory effects [4, 5]. It has been reported that ophthalmic anti-inflammatory agents such as methylprednisolone [24] and dexamethasone [7] yield effective results in dry eye cases [5]. Ophthalmic methylprednisolone has been shown in animal experiments to reduce inflammation, provide corneal epithelial surface smoothness, and maintain epithelial barrier function [25].…”
Section: Discussionmentioning
confidence: 99%
“…Studies showing that proinflammatory cytokines play a role in dry eye pathogenesis have begun to take anti-inflammatory treatment protocols to the foreground in the treatment of this disease [22, 23]. Corticosteroids are used in the inflammatory process especially in dry eye pathogenesis due to their strong anti-inflammatory effects [4, 5]. It has been reported that ophthalmic anti-inflammatory agents such as methylprednisolone [24] and dexamethasone [7] yield effective results in dry eye cases [5].…”
Section: Discussionmentioning
confidence: 99%
“…We performed the test, as previously reported in the literature, 26,30 but found no significant difference in blink rate and completeness between the control and study groups at any time point. This finding was similar to that previously described by Suwan-Apichon et al 26 Another important finding in our study was a marked decrease in the number of superior and inferior conjunctival goblet cells in the control group when compared with the HAF and HS groups.…”
Section: Discussionmentioning
confidence: 99%